An Anylisis of Figurative Language in Harmony’s Song Lyrics - Kiki Ariska; Syamsurrijal Syamsurrijal; Wahyu Kamil Syarifaturrahman (Humanitatis : Journal of Language and Literature, 2021)
The purposes of this research are: (1) to identify the types of figurative language found in Harmony’s song lyrics. And (2) what are the function of figurative language used in Harmony’s song lyrics? This research applied descriptive qualitative approach. In collecting the data, the researcher searched the songs and noting technique to the scripts. Read and understood the song lyrics in Harmony’s song lyrics. While in analyzing the data, the researcher translate the data into English, identified the data based on the types of figurative languages, classified the data based on the types of figurative languages, analyzed the selected data based on the figurative languages. The results of data analysis, there are seven data found in Harmony’s song lyrics, namely: simile, symbol, irony, personification, paradox, hyperbole, and metaphor. The function of figurative language simile and symbol in Thun Nathe’s song lyrics is to afford imagination pleasure, while in irony is to add emotional intensity. In Sauadagar Percek’s song lyrics simile is used to afford imaginative pleasure, personification and paradox is used to say much in a brief compas, while in hyperbole is to add emotional intensity. In Selaq Bonga’s song lyrics, metaphor is used to add emotional intensity.